Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1097/00006123-199708000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic Spinal Epidural Hematoma: Report of Four Cases and Review of the Literature

Abstract: We considered the expression "nontraumatic epidural hematoma" to be less ambiguous than "spontaneous spinal epidural hematoma," which is the one that is usually used in the literature and corresponds to various definitions. In the absence of any signs suggestive of vascular malformation on magnetic resonance imaging, preoperative angiography is not essential and need not delay the surgical procedure, because the timing of the surgery, together with the preoperative clinical state, determines the quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 17 publications
1
54
0
6
Order By: Relevance
“…Lonjon et al reported that the preoperative neurological status is the essential prognostic factor [18,30]. Foo et al [9] reported the neurological status returned to normal in only 45.3% of the patients among the early complete deficit patients, but the neurological status returned to normal in 95% of the patients among the incomplete sensorimotor deficit ones.…”
Section: Initial Neurological Deficit and Neurological Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Lonjon et al reported that the preoperative neurological status is the essential prognostic factor [18,30]. Foo et al [9] reported the neurological status returned to normal in only 45.3% of the patients among the early complete deficit patients, but the neurological status returned to normal in 95% of the patients among the incomplete sensorimotor deficit ones.…”
Section: Initial Neurological Deficit and Neurological Outcomementioning
confidence: 99%
“…Lonjon defined idiopathic spinal hematoma and secondarily arisen spinal hematoma in the result of coagulopathy or vascular malformation or tumor bleeding [18,30]. The standard management for SSEH is to evacuate the hematoma and perform spinal cord decompression by an emergency operation [13,32].…”
mentioning
confidence: 99%
“…7,16,20) ASEH with progressive neurological deficit should be treated by emergent evacuation of the hematoma and decompression of the spinal cord. 1,2,10,16,18,23) Multilevel ASEH requires removal of all or every other lamina of the involved spinal levels and evacuation of the hematoma. However, conservative treatment with spontaneous resolution of the hematoma may be preferred to surgical decompression.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is estimated that spontaneous spinal epidural hematomas (SSEHs) arise in B0.1 patient in every 100 000 patients, 3 with a male-female ratio of 1.4:1. 4 The clinical presentation varies depending on the spinal level affected, and can evolve very quickly from minor symptoms to a complete neurological deficit. In most cases, only early diagnosis with urgent treatment can allow the recovery of neurological function, sometimes even being vital for survival.…”
Section: Introductionmentioning
confidence: 99%